Cross-union surgery for tibiofibular fractures in McCune-Albright syndrome: a case report and literature review - Zhu, Hui; Wang, Yiwei; Zhuang, Hanjie; Zheng, Pengfei; Tang, Yuping (Frontiers in Pediatrics, 2025)
IntroductionMcCune-Albright syndrome (MAS) is a rare disease. MAS manifests in the skeletal system as Fibrous dysplasia (FD). In MAS patients, bone lesions often result in fractures under weight-bearing forces during childhood, and pseudarthrosis formation is highly likely after fractures. There is currently no ideal treatment for fractures in children with MAS. This case study presents the innovative application of the cross-union technique in treating a 14-year-old female MAS patient with a distal tibial and fibular fracture nonunion.MethodsThe patient had a history of conservative treatment with persistent symptoms, including an inability to bear weight and walk independently. A “cross-union” procedure was performed using a Fassier-Duval rod, locking plate, and K-wire fixation.ResultsAt the final follow-up 12 months postoperatively, x-rays revealed a stable “cross-union” bone connection at the distal ends of the tibia and fibula, with no occurrence of refracture or other complications. The Radiographic Union Score for Tibial Fractures (RUST) was 12, and the Olerud Molander Ankle Score was 60.ConclusionWe successfully applied the “cross-union” technique to a MAS child with nonunion after a distal tibiofibular fracture. We look forward to further improvement and promotion of the “cross-union” technology in the future, bringing new hope for treating fractures in MAS/FD children.